ANALISIS PERSEPSI KONSUMEN ANAK MUDA TERHADAP BAURAN PEMASARAN YANG DITERAPKAN OLEH PROVIDER TELKOMSEL DI KOTA PONTIANAK - B11106013, Adi Nugroho (Jurnal Manajemen Update, 2013)
Basic concepts in this research is to measure how well level consumer perceptions juvenility against hotchpotch marketing applied by telkomsel. Kotler according to consumer perceptions is a process of how individuals choose, organizes, and interpret inputs information to create image of the world having meaning. The purpose of this study is to find out how consumer perception of young people in the city of Pontianak on the marketing mix, namely 7P (product, price, promotion, place, people, physical evidence, and process) on a prepaid GSM cards products applied by providers of cellular operator Telkomsel. From the results obtained from this study may be aware that the perception of the consumers of prepaid card products telkomsel is good enough. According to young consumers. Vodacom prepaid card products have a banya, product variations of diverse tariff package choices, good sound quality, a stable signal and internet access are fairly tight. One of the things that become a problem is the price of fares being charged are too high for Telkomsel young people especially for those who are still sitting on the bench that sits in the school and collegiate bench. In order not to left by consumers especially in the segment of young people preferably Vodacom offers cheap and affordable for consumers, especially young learners and students. Because it is possible the customers of Telkomsel moved to other operators offering cheaper rates of Telkomsel.